2019
DOI: 10.18502/jnfs.v4i1.399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paleolithic Diet on Glucose Control in Adults: A Systematic Review and Meta-analysis of Controlled Clinical Trials

Abstract: Background: Although the results were conflicting, the Paleolithic diet (PD) was proposed to be effective in improvement of metabolic status. We aimed to conduct a systematic review and meta-analysis on the randomized controlled clinical trials (RCTs) evaluating the effects of PD on glycemic markers. Methods: Online databases such as PubMed, Scopus, Web of Science, and Google Scholar were searched up to December 2017 without any restrictions. The weighted mean difference (WMD) was also calculated using random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The paleo diet, and lifestyle pattern (e.g., physical activity and sleep) that quickly followed, is produced by viewing modern health from an evolutionary perspective [2]. Clinical research has demonstrated beneficial effects of following a paleo diet [3,4]. Meanwhile, the paleo diet has since been labeled as a fad diet [5,6] and is surrounded by controversy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The paleo diet, and lifestyle pattern (e.g., physical activity and sleep) that quickly followed, is produced by viewing modern health from an evolutionary perspective [2]. Clinical research has demonstrated beneficial effects of following a paleo diet [3,4]. Meanwhile, the paleo diet has since been labeled as a fad diet [5,6] and is surrounded by controversy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%